THE HISTORICAL FOOTPRINT OF INDIA-MUSLIMS IN NORTH SUMATRA: History and Management of the Al-Mukhlish Tebingtinggi Mosque - Hasan Asari; Harun Al-Rasyid; Muaz Tanjung; Muhammad Rifqi Irsyad (Journal of Contemporary Islam and Muslim Societies, 2023)
Abstract: This study aims to analyze Al-Mukhlis Mosque as an Indian-Muslims heritage at Tebing Tinggi City. Data were based on Religious Court documents and interviews of the mosque’s managers. Reliable history of the mosque could be established only since 1920s. Its historical milestones includes 1) the first waqf in 1920 by Kuti Kaka, 2) change of name to Al-Mukhlis Mosque in 1950, 3) main restoration in 1978, 4) legal waqf status by Religious Court in 1986, and 5) a total renovation in 2014. Al-Mukhlis Mosque current management is appointed by the Ministry of Religious Affairs. The mosque activities include worship, Islamic education, and general social activities. Finally, its Indian identity remains socially acknowledged because of the presence of the Indian-Muslim community as its organizer and funder. The mosque might become the starting point for the revival of Indian-Muslims’ roles of the city. Keywords: Indian-Muslim, Mosque, East Sumatra, North Sumatra, Islam